2001
DOI: 10.1902/jop.2001.72.10.1348
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Resorption Following Coronal Versus Apical Approach in a Mucoperiosteal Flap Surgery Procedure in the Rat Mandible

Abstract: The results of this study show that periodontal surgery by a coronal surgical approach stimulates a burst of remodeling of the alveolar bone in a very specific pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
2
43
0
5
Order By: Relevance
“…A later study by Binderman et al 80 showed that local remodeling of bone is greater when the flap is from a coronal approach rather than from an apical approach.…”
Section: Periosteal Flaps and The Rapmentioning
confidence: 98%
“…A later study by Binderman et al 80 showed that local remodeling of bone is greater when the flap is from a coronal approach rather than from an apical approach.…”
Section: Periosteal Flaps and The Rapmentioning
confidence: 98%
“…It seems that the separation of the gingiva from the tooth and disruption of the dento‐gingival fibers rather than separation of the mucoperiosteum from the alveolar bone is the major trigger for alveolar bone loss 4 . Alveolar bone loss commences only when vertical sectioning of the collagen bundles of the gingiva by a coronal approach (COR) is performed in contrast to an apical surgical approach (AP) 5 . It was also noted that discarding the sectioned marginal gingiva, including the cells, prevented alveolar bone resorption 2,6 .…”
mentioning
confidence: 99%
“…Three weeks later, a significant bone loss on the periodontal aspect of alveolar bone that extends toward bone crest was recorded [4,18]. In the present study, human gingival fibroblasts (HGF) that were seeded on collagen coated culture dishes normally developed traction forces between the HGF cells and collagen [27][28][29].…”
Section: Discussionmentioning
confidence: 70%
“…Externally applied forces are transmitted by integrins or cadherins into and throughout the cell toward the nuclear membrane, by adhesive proteins that link to cytoskeleton structures [2]. Our previous studies [3][4][5] and others [6,7] have shown that surgical detachment of dento-gingival fibers from root surfaces is a major trigger for alveolar bone resorption, in a rat model because a sudden reduction of physiological strains of adherent fibroblasts ensued [8]. We found that a rapid release of ATP from the cells to the extracellular environment and up-regulated expression of ATP cell membrane receptor P2X4 is main trigger for alveolar bone resorption [9].…”
Section: Introductionmentioning
confidence: 98%